Analysis of Polish mutual funds performance: a Markovian approach - Dariusz Filip; Tomasz Rogala (Statistics in Transition New Series, 2021)
The aim of this study is to determine whether mutual funds provide benefits for their clients. The performance of Polish mutual funds has been evaluated in terms of their efficiency, including their potential inertia over time. Moreover, the use of the phenomenon of economies of scale resulting from assets inflow to the fund by means of the Markovian framework has been examined. The results are consistent with the efficient market hypothesis. When assessing the market-adjusted returns, underperformance was noticed in both small and large funds. The smart money effect, recognised in the literature, is not confirmed here; however, there are some noticeable investor reactions, such as the phenomenon of chasing performance.
Keywords: 519; Markov chain; smart money effect; effectiveness; performance inertia